Basic principles of induction logging electromagnetic methods in borehole geophysics - Kaufman, Alexander; Itskovich, Gregory (Amsterdam Elsevier, 2017)
Basic Principles of Induction Logging provides geoscientists with the information required to survey the electrical conductivity of rocks surrounding a borehole. The formation conductivity distribution in the borehole vicinity is critical information required in formation evaluation and geosteering applications. Developing a theory of EM logging and on understanding basic physics for both wireline and LWD logging tools, this reference furnishes valuable insights for development and use of EM techniques in practical logging applications. Basic Principles of Induction Logging will be vital for anyone attempting to investigate, invent, and develop the next generation of EM logging tools. It will provide information required to enable operation in more challenging environments such as logging while drilling, anisotropic and thinly laminated formations, high angle and horizontal wells.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Induction logging; Electronic books